Agrobiodiversity conservation policies: Insights from an integrated micro-macro economic model in Ethiopia - Gotor, Elisabetta; Orecchia, Carlo; Pallante, Giacomo; Fadda, Carlo; Salvatici, Luca (Springer, 2025)
National strategies aiming to enhance agricultural productivity in sub-Saharan Africa have traditionally focused on encouraging the adoption of improved modern crop varieties. This approach led to genetic erosion and reduced option value for bioprospecting, an unintended consequence of the decline of locally conserved traditional varieties. Governments are often left with poor guidance to evaluate the costs and benefits of this strategy. In this paper, we propose a methodological framework for assessing agricultural policies based on local agrobiodiversity conservation. In particular, we modify a computable general equilibrium model with trade to account for the land allocated to traditional and improved modern varieties as input for the agricultural sector. As a case study we select the Ethiopian durum wheat. Several sources of data at macro, micro and agronomic levels are adopted to estimate parameters and economic effects. Accounting for climate change and technological projections up to 2050, results of a counterfactual scenario show that when policy-driven breeding programs in specific agroecological niches are implemented, they simultaneously achieves conservation and food production goals. The findings underscore the need for policy interventions aimed at promoting context-specific strategies that consider conservation and production objectives within the broader agricultural landscape.